Nonalcoholic fatty liver disease and metabolic syndrome: Shared genetic basis of pathogenesis - Sookoian, Silvia Cristina (2016)
A growing body of evidence indicates that nonalcoholic fatty liver disease (NAFLD) develops from a complex process that includes genetic susceptibility and environmental exposure. Regardless of whether it is the cause or the consequence of the metabolic syndrome (MetS), NAFLD often co-occurs with one or more MetS-associated phenotypes. There is also robust evidence in support of NAFLD and MetS sharing common pathogenic mechanisms.(1) Nevertheless, with the exception of the transmembrane 6 superfamily member 2 gene(2)— which illustrates an unexpected opposite association between NAFLD and cardiovascular disease, although it can be suspected—no compelling report demonstrating that NAFLD and MetS share a common genetic background presently exists. In this issue, Cui et al. show not only that steatosis and fibrosis potentially share the same predisposing genes but also that these conditions have a significant shared gene effect with metabolic risk factors,(3) the latter being a truly remarkable finding. These interesting results prompt several reflections.